2005
DOI: 10.1007/s00412-005-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Replication of heterochromatin: insights into mechanisms of epigenetic inheritance

Abstract: Heterochromatin is composed of tightly condensed chromatin in which the histones are deacetylated and methylated, and specific nonhistone proteins are bound. Additionally, in vertebrates and plants, the DNA within heterochromatin is methylated. As the heterochromatic state is stably inherited, replication of heterochromatin requires not only duplication of the DNA but also a reinstallment of the appropriate protein and DNA modifications. Thus replication of heterochromatin provides a framework for understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 109 publications
2
44
0
Order By: Relevance
“…CyclinE genetically interacts with proteins known to affect chromatin structure (51), and thus it is conceivable that in the cyclinE 1f36 mutant the chromatin configuration is altered to be more permissive for replication fork progression. We did not observe histone acetylations associated with replication forks during amplification (52), so it is unclear what modifications or binding proteins would change the accessibility of chromatin for fork movement (53).…”
mentioning
confidence: 71%
“…CyclinE genetically interacts with proteins known to affect chromatin structure (51), and thus it is conceivable that in the cyclinE 1f36 mutant the chromatin configuration is altered to be more permissive for replication fork progression. We did not observe histone acetylations associated with replication forks during amplification (52), so it is unclear what modifications or binding proteins would change the accessibility of chromatin for fork movement (53).…”
mentioning
confidence: 71%
“…Thus, before the packaging of the chromatin to higher order structures, chromatin modification must occur. Heterochromatin assembly also involves HP1, which binds to H3K9 di-and trimethylated (Jacobs et al 2004;Wallace and Orr-Weaver 2005). HP1 interacts with p150, the large subunit of CAF-I, suggesting that CAF-I may participate in HP1 redistribution on heterochromatin during replication (Murzina et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic information carried by the heterochromatin structures has to be transmitted to daughter cells after cell division in what is known as replication-coupled epigenetic memory (Wallace and Orr-Weaver, 2005). The faithful inheritance of hallmarks such as H3K9me3, H4K20me3 and HP1 on the daughter strands of DNA ensures the integrity and stability of heterochromatin.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies suggested the epigenetic involvement of CAF-1 in the re-establishment of chromatin after DNA replication and/or repair. Furthermore, it has been proposed that CAF-1 might play a crucial role in organizing the actions of the heterochromatin components during heterochromatinization (for reviews, see Groth et al, 2007;Wallace and Orr-Weaver, 2005). This proposal was based on emerging in vivo evidence that CAF-1 dysfunction can cause heterochromatin abnormality in various organisms such as mouse (Houlard et al, 2006), Xenopus (Quivy et al, 2001), Drosophila (Song et al, 2007), Saccharomyces cerevisiae (Monson et al, 1997), Schizosaccharomyces pombe (Dohke et al, 2008) and Arabidopsis (Ono et al, 2006;Schonrock et al, 2006).…”
Section: Introductionmentioning
confidence: 99%